Boosting uranium adsorption performance by engineering flexible linkers in tannin-immobilized polyamide membranes - Hongru Zhang; Linping Yan; Zihe Li; Wei Luo; Xuepin Liao; Bi Shi (Desalination, 2026)

Azo-sulfonate functionalized collagen fibers for rapid and high-capacity uranium capture - Zihe Li; Linping Yan; Wei Luo; Xuepin Liao; Bi Shi (Chemical Engineering Journal, 2026)

Achieving 99% selective photocatalytic conversion of CO2 to CH4 via built-in electric field guided S-scheme charge transfer in UiO-66/CuS heterojunction - Jia Shi; Xiaoqing Shi; Linping Li; Kezhen Lai; Yanping Qiu; Ning Li; Yangqin Gao; Lei Ge (Chemical Engineering Journal, 2026)

Photodegradation behavior of different polyurethane: A comparison study of foam and leather - Linping Shi; Zhimin Gong; Minjie Xie; Wen Shao; Houru Cheng; Shixiang Gao (Journal of Environmental Sciences, 2026)

Rapid on-site quantification of total polar materials in edible oils via a polarity-triggered fluorescent probe and smart 3D-printed sensing platform - Tianhua Ma; Chiyuan Wei; Siyu Shi; Lanlan Yu; Linping Zhao; Yuanqiang Sun; Zhaohui Li (Food Chemistry, 2026)

Decoding synergy: from the precise construction of dual-atom catalysts to synergistic engineering - Yaning Fu; Linping Shi; Dongxue Liu; Yipeng Liu; Tong Liu; Yunyin Niu; Youcai Lu; Qingchao Liu (Chemical Engineering Journal, 2026)

Analysis of aged microplastics: a review - Yanqi Shi; Linping Shi; Hexinyue Huang; Kefu Ye; Luming Yang; Zeena Wang; Yifan Sun; Dunzhu Li; Yunhong Shi; Liwen Xiao; Shixiang Gao (Environmental Chemistry Letters, 2024)
Microplastics are emerging contaminants that undergo progressive aging under environmental conditions such as sunlight irradiation, mechanical forces, temperature variations, and the presence of biological organisms. Since aging modifies microplastic properties, such as their own toxicity and the toxicity of trapped pollutants, advanced methods to analyze microplastics are required. Here we review methods to analyze microplastic aging with focus on the aging process, qualitative identification, quantitative characterization, and chemometrics. Qualitative identification is done by mechanical techniques, thermal techniques, e.g., thermal degradation and gas chromatography–mass spectrometry, and spectral techniques, e.g., infrared, Raman, fluorescent, and laser techniques. Quantitative characterization is done by microscopy and mass spectrometry. Microplastic aging results in a series of surface physical changes, biofilm formation, chemical oxidation, thermal alternation, and mechanical deterioration. Changes in mechanical and thermal properties allow to differentiate aged microplastics. Infrared and Raman spectroscopy are rapid and sensitive for chemical identification of microplastics in complex environmental samples. Combining two techniques is preferable for accurate detection and categorization.

Interactions between methyl octabromo ether flame retardant and expanded polystyrene microplastics in the photoaging process - Yanqi Shi; Lezhou Zheng; Hexinyue Huang; Linping Shi; Zhimin Gong; Kefu Ye; Xingqi Chen; Shixiang Gao (Chemosphere, 2024)

Formation of Sb2O3 microcrystals by Rhodotorula mucilaginosa - Linping Yang; Aijiang Yang; Liyan Song; Wen Cui; Wanping Bian; Aping Niu; Peng Xu; Shouyang He; Shixue Mei; Xianrong Shi (Journal of Hazardous Materials, 2024)

The highly effective cadmium-resistant mechanism of Pseudomonas aeruginosa and the function of pyoverdine induced by cadmium - Shixue Mei; Wanping Bian; Aijiang Yang; Peng Xu; Xiaoli Qian; Linping Yang; Xianrong Shi; Aping Niu (Journal of Hazardous Materials, 2024)

Flexible and wearable functional materials for ionizing radiation Protection: A perspective review - Hao Li; Linping Yan; Jibo Zhou; Yaping Wang; Xuepin Liao; Bi Shi (Chemical Engineering Journal, 2024)

Rapid quantitative evaluation of total polar materials (TPM) in frying oil based on an “off-on” fluorescence viscosity response probe - Jiayi Shi; Jian Tao; Yanfeng Fu; Linping Zhao; Ran Yang; Lingbo Qu; Zhaohui Li; Yuanqiang Sun (Analytica Chimica Acta, 2024)

Barbican-inspired bimetallic core–shell nanoparticles for fabricating natural leather-based radiation protective materials with enhanced X-ray shielding capability - Hao Li; Jibo Zhou; Linping Yan; Rui Zhong; Yaping Wang; Xuepin Liao; Bi Shi (Chemical Engineering Journal, 2023)